Access to general practice during COVID-19: a cross-sectional view of the opinions of adults who use social media - Mineva, Gabriela; Kiroplis, Irene; Rogers, Bethany; Pearl, Dana; Abohalima, Yasmin; O'Donnell, Patrick; McCool, Aoibhin; Hayes, Peter; Volz, Monika (Annals of family medicine, 2022)
Background/Aim: Since the onset of the COVID-19 pandemic, virtual consultations have become commonplace, and access to healthcare more complex. The study was designed to examine the impact COVID-19 has had on access to general practice care in Ireland. Methods: A 25-question online survey was designed in Qualtrics®. Adult patients of Irish general practices were recruited via social media between October 2020 and February 2021 and volunteered their opinions. Results: 670 persons participated. Half of all doctor-patient consultations were now completed virtually-predominantly via telephone. Overall, 497 (78%) participants accessed their healthcare teams as scheduled, and without disruption. 18% of participants (n=104) reported difficulty in accessing their long-term medications; those who are younger, and those who typically attend general practice quarterly or more, were associated most with this disruption (p<0.05). Fifty-nine instances where a new health concern was subject to an appointment cancellation or rescheduling were reported. Conclusions: Despite the COVID-19 pandemic, Irish general practice has maintained its schedule for appointments in 78% of cases despite the challenges of the pandemic. Half of consultations were provided virtually; teleconsultation use was very infrequent. Maintaining the supply chain for long-term medications for patients remains a challenge during a pandemic. Authors accept that study participants were confined to those who use social media. A protocol may need to be designed by each practice to optimize the continuation of care and of medication schedules during any future pandemics.